Digitalisasi Informasi Nagari melalui WEB : Strategi untuk Menjaga Budaya dan Meningkatkan Akses Informasi - Refy Faustina Khairani; Samuel Martin; Dalman Marsallailan; Hasri Zulhani; Prisca Leonisa Maorin; Sarah Fadya Ahmad; Yola Triana (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
The history, culture, and Islamic values of Nagari Sumpur Kudus in Sijunjung Regency, West Sumatra, are very rich, but still lack digital documentation. Local heritage, such as the spread of Islam by Sheikh Ibrahim, the traditional governance system of Rajo Ibadat, and the role of Sumpur Kudus in the Emergency Government of the Republic of Indonesia (PDRI), is scattered in oral stories, collective memory, and local documents that are difficult for the public to access. This condition has led the younger generation to become less familiar with their own history and local identity, which may result in cultural gaps. Through the development of a website based on the culture and history of Nagari Sumpur Kudus, this study aims to record and digitize the local history. Digitalization is considered essential as it allows historical values to be properly preserved and widely, quickly, and sustainably accessed. This effort supports the preservation of cultural heritage in the modern era. To produce a comprehensive representation, a qualitative-descriptive approach was used to collect data, which included field observations, document studies, and semi-structured interviews with local people, religious leaders, and traditional leaders. Descriptive analysis was carried out to interpret the meaning of each source. The results show that digitalization through a website is capable of archiving historical values in a systematic, interactive, and accessible way. Moreover, the website serves as a medium for education, cultural promotion, and strengthening local identity amid globalization. It also has the potential to become a model for community-based local history preservation that is adaptive to technological developments and supports the development of cultural tourism in Nagari Sumpur Kudus.